Meningkatkan Taraf Hidup Dan Kebersihan Lingkungan Masyarakat Kenten Dengan Pemanfaatan Maggot Sebagai Pengurai Sampah Organik - Fernando Africano (Jurnal Pengabdian Masyarakat Akademisi, 2022)
Kenten Village is one of the villages in Banyuasin Regency with a fairly high population density. High population density certainly affects the surrounding environment, one of which is waste. In 2022, the Ministry of Environment and Forestry predicts there will be 35 million kilograms of waste, which is dominated by household waste. For now, various solutions have emerged to deal with this waste issue. Therefore, the Village Community Empowerment Program (P2MD) team carried out a program with the theme Empowerment of Waste Processing in the Community by Utilizing Maggot BSF (Black Soldier Fly) as a Waste Decomposer. This program is carried out by the extension method. There are several stages carried out in this program, namely observation, program planning, socialization, program implementation, and evaluation. The results of this program are the creation of a clean environment in the Kenten village, and an increase in economic value which is the sale of the results of the decomposition of organic waste with Maggot BSF.